HUBUNGAN INTENSITAS PENCAHAYAAN, KELELAHAN MATA DAN GANGGUAN KETAJAMAN PENGLIHATAN PADA PEKERJA BAGIAN INSPECTING PT. TEKSTIL X - Intan Alfina Khoiriyah; Siswi Jayanti; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Comfortable lighting intensity was very needed on work that requires using eye skills, concentration and high accuracy, especially the monotonous work process. One of the stages monotonous work process was the inspecting section work that requires high accuracy in aligning the colors, inspecting the grey thread, and determining the quality product. During initial survey, it was found that the local lighting intensity was 103 lux on the manual table and 135 lux on the machine table while under the lighting standard. The purpose of this research was to analyze the correlation between the lighting intensity, eye fatigue, and visual acuity disturbance. This research was using observational analytic method and cross sectional studies. The sampling technique was using total sampling method taking population of inspecting section workers, which was about 74 people that divided on the morning shift and afternoon shift. Lighting intensity is measured by luxmeter, eye fatigue measured by the reaction timer and visual acuity measured by snellen chart. Bivariate analysis with Rank Spearman correlation results in shows a significant relationship of lighting intensity to eye fatigue ρvalue of 0,001<0.05, a significant relationship of fatigue eyes on visual acuity disturbances ρvalue 0.043 <0.05, and a significant correlation between the lighting intensity on visual acuity disturbance ρvalue 0,001<0,05. Companies were needed to carry out regular eye checks, increase lighting intensity by increasing the power of lights, and workers should keep eye healthy and prevent eye fatigue.